Analisis Dampak Permainan Daring Mobile Legends terhadap Prestasi Belajar Siswa Sekolah Dasar - Rafi Arya Putra P (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
he rapid advancement of information technology has significantly influenced various aspects of human life, including education. One of the technological developments that has attracted considerable attention is the increasing popularity of online games among school-aged children. Mobile Legends is one of the most widely played online games in Indonesia and has both positive and negative impacts on students. This study aims to analyze the effects of playing Mobile Legends on elementary school students' learning achievement. The research employed a qualitative approach using a literature review method. Data were collected from scientific journal articles, books, and relevant previous studies discussing online gaming and students' academic achievement. The findings indicate that playing Mobile Legends may provide several positive effects, such as improving concentration, strategic thinking, teamwork, English language skills, and expanding social interactions. However, excessive gaming has more dominant negative impacts, including addiction, reduced learning motivation, decreased concentration during classroom activities, eye health problems, limited social interaction, and declining academic achievement. Therefore, parental supervision and effective time management are essential to ensure that online gaming activities do not interfere with students' learning responsibilities. Schools also play an important role in educating students about responsible digital entertainment.